Social effects of digital pornography - Saputra, Muhammad Firman Aji; Siregar, Sherly Allsa; Izdihar, Zahra Nabila (Bulletin of Social Informatics Theory and Application, 2017)
Emerging technology will provide benefits for users. Especially with the presence of the internet will make technology more perfect. On the one hand, technology and the internet provide benefits, on the other hand can also give a negative impact for users, one of which is the rise of pornographic content on the internet or often called cyberporn. With the internet, pornography can be obtained easily. That's because the producers of pornographic content think that the internet is the most optimal marketing medium. The presence of pornography has occurred pros and cons in various countries. In Indonesia, it is strictly prohibited because it can damage the morale of the next generation of the nation. In addition, pornography is something very addictive to humans that will eventually happen in various things. In fact, porn addiction is more severe addictive substance addiction than psychotropic. Some efforts that can be done to minimize the pornography deal either by the government of Indonesia, family, or other related parties are making laws that regulate pornography, blocking pornographic sites, providing early childhood sex education, and the role of parents in child supervision.